Investigation of flank wear in MQL milling of ferritic stainless steel by using nano graphene reinforced vegetable cutting fluid - Uysal, Alper (EMERALD GROUP PUBLISHING LTD, 2016)
Purpose - In milling of stainless steel materials, various cutting tool failures such as flank wear, crater wear, cracks, chipping, etc. can be observed because of their work hardening tendency and low thermal conductivity. For this reason, this paper aims to develop some coolants and coatings to reduce these formations. However, further research should be performed to reach the desired level. Design/methodology/approach - In this study, the initial flank wear rates of uncoated and titanium nitride-coated tungsten carbide cutting tools were investigated during the milling of AISI 430 ferritic stainless steel. The milling experiments were conducted under dry and minimum quantity lubrication (MQL) conditions. Nano graphene reinforced vegetable cutting fluid was prepared and applied by the MQL system. The mixture ratios of nanofluids were selected as 1 and 2 wt.%, and MQL flow rates were adjusted at 20 and 40 ml/h. Findings - It was observed that MQL milling with nano graphene reinforced cutting fluid has advantages over dry milling and MQL milling with pure cutting fluid in terms of the initial flank wear. Originality/value - This paper contains new and significant information adequate to justify publication. MQL is a new method for vegetable cutting fluid containing nano graphene particles.
Keywords: MQL; Nanofluid; Flank wear; Ferritic stainless steel; Nano graphene; MINIMUM QUANTITY LUBRICATION; PVD TIN/TAN; PERFORMANCE; TOOLS; Engineering